Becoming transnational youth workers : independent Mexican teenage migrants and pathways of survival and social mobility - Martínez, Isabel, 1979- (Latinidad., 2019)
Becoming Transnational Youth Workers contests mainstream notions of adolescence with its study of a previously under-documented cross-section of Mexican immigrant youth. Preceding the latest wave of Central American children and teenagers now fleeing violence in their homelands, Isabel Martinez examines a group of unaccompanied Mexican teenage minors who emigrated to New York City in the early 2000s. As one of the consequences of intractable poverty in their homeland, these emigrant youth exhibit levels of agency and competence not usually assigned to children and teenage minors, and disrupt mainstream notions of what practices are appropriate at their ages. Leaving school and family in Mexico and financially supporting not only themselves through their work in New York City, but also their families back home, these youths are independent teenage migrants who, upon migration, wish to assume or resume autonomy and agency rather than dependence. This book also explores community and family understandings about survival and social mobility in an era of extreme global economic inequality.